AI Enhanced Constructionism for Educational Game Design (Constructionism Conference Proceedings, 2025)
This paper describes and discusses how AI enhanced constructionism could be involved to stimulate active learning in a course on game-based learning. The main objective in the course is to create artefacts that could be combined to a game prototype at the end of the course, in the spirit of Seymour Papert’s idea of learning building meaningful artefacts. Design science research was used to gather requirements and to create the syllabus and the course design that is presented in this paper. Since the course has not been given yet, this is work in progress, but with ideas for how to combine constructionism with artificial intelligence in a course on game-based learning. The paper also discusses how to outline assignments and how to handle assessment when generative AI tools are used by course participants. Other suggested concepts for enhancing constructionism are heutagogy, feedforward and ungrading, especially if the course is given as professional development for adult learners.